Basic density, diameter and radial variation of Vanuatu Whitewood (Endospermum medullosum): potential for breeding in a low density, tropical hardwood. (1st December 2012) - Settle, D.J.; Page, T.; Bush, D.; Doran, J.; Sethy, M.; Viji, I.
Vanuatu whitewood (Endospermum medullosum L.S. Smith) is an economically important timber species for Vanuatu. Inter- and intraprovenance genetic parameters for stem diameter at breast height, basic density and radial variation in density, were estimated for two provenances selected from a 12.4-year-old open-pollinated seed orchard on Espiritu Santo Island, Vanuatu. Kole provenance exhibited the highest mean basic density, greatest mean diameter and greatest radial variation in density across the stem. Mean basic density at breast height was 345±2 kg/m3. Growth rings were not visually discernable and colour was homogenous across all samples. For radial variation determination, each pith-bark core was sectioned into four equi-length subcores (A-D). Subcore density increased consistently and significantly from pith to bark, with mean basic density of 308±3, 327±3, 343±3 and 359±3 kg/m3 for cores A-D respectively. The narrow-sense heritability estimate (h2) was low (0.26±0.2) for diameter, with a moderate coefficient of additive genetic variation ( CVA = 17.61%). Estimated h2 for density was moderate (0.49±0.24), with a low coefficient of additive genetic variation (CVA = 5.39%). Though the precision of these estimates is modest, reflective of the small sample size, indications are that the heritable genetic variation in both growth and quality traits will result in economic gain from a recurrent selection and breeding program. Vanuatu whitewood est une espèce de bois économiquement importants pour le Vanuatu. Les paramètres génétiques pour le diamètre de la tige (DBH), la densité de base (DEN) et de la variation radiale (RadVar) ont été estimés en deux provenances pendant 12, 4 années sur l'élevage de la population Endospermum medullosum L.S. Smith à pollinisation libre sur île d'Espiritu Santo, au Vanuatu. La provenance Kole a été exposée au plus haut de la densité moyenne de base, au plus haut diamètre moyen et à la plus grande variation de la densité dans la tige. Les estimations d'héritabilité (h2) (0, 26±0, 2) ont été faibles pour le DBH, avec une variation phénotypique modérée (CVA = 17, 61%) et une estimation de l'héritabilité (0, 49±0, 24) ce qui étaient modérées pour la densité, avec une variation phénotypique faible (CVA = 5, 39%). La densité moyenne de base à hauteur de poitrine était de 345 (SE±2) kg/m3, et a augmenté de façon constante 308 (SE±3), 327 (SE±3), 343 (SE±3) et 359 (SE±3) kg/m 3 et significative de la moelle à l'écorce. La faible taille de l'échantillon disponible peut avoir réduit la précision, toutefois il est prévu que le gain économique dû à la croissance et aux caractères de qualité peuvent être obtenue à partir d'une sélection récurrente et programme d'élevage étant donné les variations génétiques héréditaires indiqué dans cette étude.La madera blanca (Endospermum medullosum L.S. Smith) es una especie maderera de importancia económica para Vanuatu. Se estimaron parámetros genéticos dentro y entre procedencias para diámetro de tallos a la altura del pecho, densidad básica y variación radial en densidad para dos procedencias seleccionadas de un huerto de semillas de polinización abierta de 12.4 años de antigüedad en la isla de Espiritu Santo, Vanuatu. La procedencia Kole exhibió la mayor densidad básica, el mayor diámetro medio y la mayor variación radial en densidad a lo largo del tallo. La densidad básica media a la altura del pecho fue 345±2 kg/m3. No se pudieron discernir anillos de crecimiento en las muestras. Para la determinación de la variación radial, cada núcleo de médula de la corteza se seccionó en sub-núcleos de igual longitud (A-D). La densidad de sub-núcleos incrementó consistente y signficativamente de médula a corteza con los núcleos (A-D) exhibiendo una densidad media básica de 308±3, 327±3, 343±3 y 359±3 kg/m3 respectivamente. Las estimas de heredabilidad (h2 0.26±0.2) fueron bajas para el diámetro, con un coeficiente moderado de variación genética aditiva (CVA = 17.61%). Las estimas de heredabilidad (h2 0.49±0.24) fueron moderadas para la densidad, con un coeficiente bajo de variación genética aditiva (CVA = 5.39%). El pequeño tamaño de muestra puede reducir la precisión de estas estimas. Se espera que dada la variación genética heredable indicada en este estudio, sería posible una ganancia económica tanto en caracteres de crecimiento como de calidad a través de una selección recurrente y un programa de cultivo.